2013
DOI: 10.1590/s2176-94512013000100011
|View full text |Cite
|
Sign up to set email alerts
|

Angle Class II correction with MARA appliance

Abstract: It was concluded that the MARA appliance proved effective in correcting Angle's Class II, division 1 malocclusion while inducing skeletal changes and particularly dental changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
43
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(58 citation statements)
references
References 26 publications
13
43
2
Order By: Relevance
“…The meta-analysis showed a 1.16 mm/y increase in the total mandibular length of the MARA group over controls (WMD 5 1.16; 95% CI 5 0.61, 1.72; x 2 test 5 7.32; 5 df; P 5 .20; I 2 5 32%; test for overall effect, Z 5 4.11 and P # .0001) (Figure 1). Sensitivity analysis excluding the three lowquality studies 5,6,19 showed comparable findings (WMD 5 1.12; 95% CI 5 0.60, 1.63) ( Table 5).…”
Section: Short-term Effects Of Maramentioning
confidence: 69%
See 4 more Smart Citations
“…The meta-analysis showed a 1.16 mm/y increase in the total mandibular length of the MARA group over controls (WMD 5 1.16; 95% CI 5 0.61, 1.72; x 2 test 5 7.32; 5 df; P 5 .20; I 2 5 32%; test for overall effect, Z 5 4.11 and P # .0001) (Figure 1). Sensitivity analysis excluding the three lowquality studies 5,6,19 showed comparable findings (WMD 5 1.12; 95% CI 5 0.60, 1.63) ( Table 5).…”
Section: Short-term Effects Of Maramentioning
confidence: 69%
“…18 Therefore, only seven retrospective clinical controlled studies met the inclusion criteria. 5,6,8,9,[19][20][21] The participants were growing subjects with Class II division 1 malocclusion in all studies except for one in which the type of Class II malocclusion was not specified. 6 The age ranges were 10.11-12.3 years for the MARA subjects (N 5 180) and 11.63-11.9 years for the control subjects (N 5 126).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations